PENGARUH LATIHAN SKIPPING ROPE TERHADAP POWER OTOT TUNGKAI PADA PEMAIN BOLA BASKET EKSTRAKULIKULER PUTERA SMA HANDAYANI - Putra, Septiandi Rory Ahmad; ', Slamet; ', Yuherdi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: the effect of skipping rope exercise toward leg muscle power of basketball extracurricular players in SMA Handayani Pekanbaru. This research was conducted to find out the effect of skipping rope exercise toward leg muscle power of male basketball extracurricular players in SMA Handayani Pekanbaru. This research was quasy experiment and the design of the research used one group pre test post test design. The population in this research consisted of all male players of basketball extracurricular of SMA Handayani Pekanbaru. There were 22 players. The technic of taking sample in this research used purposive sampling and the researcher took male students of class X and XI with 12 students. The data were analyzed by using t test. The result of the research showed that there was the effect of skipping rope exercise toward leg muscle power of male basketball extracurricular players in SMA Handayani Pekanbaru. The average was 45,83 in pretest and 56,25 in posttest with the different mean was 10,42 (Ttest was 3,11 and Ttable was 1,796)Keyword : skipping rope exercise, leg muscle power, Basketball